ANALISA ATRIBUT HOTEL YANG MENDORONG MINAT MENGINAP MASYARAKAT INDONESIA TERHADAP HOTEL BINTANG 4 DAN 5 DI BALI - Ryan Kurniawan Njoto; Leonanta Pradana Sujarwo Putra; Monika Kristanti (Jurnal Hospitality dan Manajemen Jasa, 2019)
AbstrakPenelitian ini dilakukan untuk mengetahui lebih jauh mengenai atribut hotel yang mendorong minat menginap masyarakat Indonesia terhadap hotel bintang 4 dan 5 di Bali. Teknik analisa yang digunakan dalam penelitian ini adalah statistik deskriptif dengan menggunakan analisa faktor untuk mengelompokkan atribut- hotel yang ada ke dalam beberapa kelompok faktor. Hasil penelitian ini menunjukkan bahwa terdapat 11 faktor yang mempengaruhi minat menginap masyarakat Indonesia di hotel bintang 4 dan 5 di Bali: facility and service, staff profesionalism and room cleanliness,health facilities and availibility of bar, hotel image and availibility of green space, room comfort and cleanliness of public areas, pleasure and expenditure, availibility of parking area and safety factors, hotel website presentation, value for money and ambience, hotel’s loaction and tourist attraction, food and beverages quality. Faktor facility dan service merupakan faktor yang paling berpengaruh terhadap minat menginap masyarakat Indonesia untuk menginap di hotel bintang 4 dan 5 di Bali.Kata kunci: Atribut Hotel, Minat Menginap, Hotel bintang 4 dan 5 di Bali.AbstractThis research is accomplished to explore more about the hotel attributes that encourages Indonesian people intention to stay in 4 and 5 star hotels in Bali. The analysis technique used statistic descriptive and used factor analysis to group several hotel attributes into several groups of factors. The result shows that there are 11 factors that encourages Indonesian people intention to stay in 4 and 5 star hotels in Bali: facility and service, staff profesionalism and room cleanliness,health facilities and availibility of bar, hotel image and availibility of green space, room comfort and cleanliness of public areas, pleasure and expenditure, availibility of parking area and safety factors, hotel website presentation, value for money and ambience, hotel’s loaction and tourist attraction, food and beverages quality. Facility and service factors is the most influental for Indonesian people to stay in 4 and 5 star hotels in Bali.Keywords : Hotel Attributes, Intention to Stay, 4 and 5 Star Hotels in Bali.